Accuracy and precision of the RABBIT technique. (1st April 2019) - Isinger, M.; Busto, D.; Mikaelsson, S.; Zhong, S.; Guo, C.; Salières, P.; Arnold, C. L.; L'Huillier, A.; Gisselbrecht, M.
Abstract : One of the most ubiquitous techniques within attosecond science is the so-called reconstruction of attosecond beating by interference of two-photon transitions (RABBIT). Originally proposed for the characterization of attosecond pulses, it has been successfully applied to the accurate determination of time delays in photoemission. Here, we examine in detail, using numerical simulations, the effect of the spatial and temporal properties of the light fields and of the experimental procedure on the accuracy of the method. This allows us to identify the necessary conditions to achieve the best temporal precision in RABBIT measurements. This article is part of the theme issue 'Measurement of ultrafast electronic and structural dynamics with X-rays'.